2007
DOI: 10.1088/0957-0233/19/1/015509
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting kinetic inductance detectors for astrophysics

Abstract: The kinetic inductance detector (KID) is an exciting new device that promises high-sensitivity, large-format, submillimetre to x-ray imaging arrays for astrophysics. KIDs comprise a superconducting thin-film microwave resonator capacitively coupled to a probe transmission line. By exciting the electrical resonance with a microwave probe signal, the transmission phase of the resonator can be monitored, allowing the deposition of energy or power to be detected. We describe the fabrication and low-temperature tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…The only difference was in a single measurement on a Nb resonator, when two discontinuities where seen when sweeping the frequency in the same direction. 42 This observation can now be understood in terms of an inadvertent double-dip on the power absorption curve of the resonant circuit, leading to three stable and two unstable quasiparticle temperature states.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The only difference was in a single measurement on a Nb resonator, when two discontinuities where seen when sweeping the frequency in the same direction. 42 This observation can now be understood in terms of an inadvertent double-dip on the power absorption curve of the resonant circuit, leading to three stable and two unstable quasiparticle temperature states.…”
Section: Discussionmentioning
confidence: 98%
“…A detailed experimental study is needed before this question can be answered but it is interesting to note that Nb resonators show, experimentally, the same general behavior as our simulations predict. 42 …”
Section: B Niobium and Tantalummentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Such resonators are also being used in quantum computing experiments [8][9][10] and for sensing nanomechanical motion. 11 We previously reported that excess frequency noise is universally observed in these resonators and suggested that two-level systems ͑TLSs͒ in dielectric materials 14,15 may be responsible for this noise.…”
mentioning
confidence: 99%
“…The noise decreases by nearly two orders of magnitude as the temperature is increased from 120 to 1200 mK, while the variation of the resonance frequency with temperature over this range agrees well with the standard two-level system ͑TLS͒ model for amorphous dielectrics. Superconducting microresonators are useful for photon detection, [1][2][3][4][5][6][7] coupling to qubits, [8][9][10] superconducting quantum interference device multiplexers, 11,12 and studying basic physics. [13][14][15][16] Such resonators have excess noise 2,17 that is equivalent to a jitter of the resonance frequency, likely caused by two-level tunneling systems ͑TLSs͒ in amorphous dielectrics.…”
mentioning
confidence: 99%